Buttons of San Juan: Preliminary Analysis of Buttons Recovered from San Juan, Batangas 2009 Field Season - Basilia, Pauline A. (Hukay, 2014)
The 14 buttons recovered from the 2009 excavation of Structure A, Barangay Pinagbayanan, San Juan, Batangas were morphologically and chemically analysed using Energy Dispersive X-ray (EDS). The objective of the analysis is to determine the raw material of the buttons for classification. Optical microscopy reveals breakage pattern, patina, and manufacturing traces indicative of glass buttons. After EDS analysis, five button types were identified: porcelain or prosser buttons, glass type 1, 2 and 3 buttons, glass shanked button, and a bone button. Based on the known button manufacturing lifetimes, it is suggested that all inorganic buttons were European imports with prosser buttons possibly from a Bapterosses factory in France.